2013
DOI: 10.1002/jhbp.61
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial on timing and number of sampling for bile aspiration cytology

Abstract: Bile cytology positivity is unlikely to be affected by sample time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Despite the use of advanced imaging techniques, diagnosis is uncertain [ 22 ]. Moreover, studies have found that 3–17 % of patients with suspected malignant stenosis were eventually diagnosed with a benign lesion through postoperative histological examination [ 23 , 24 ]. In many cases, diagnosis is based on bile cytology.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the use of advanced imaging techniques, diagnosis is uncertain [ 22 ]. Moreover, studies have found that 3–17 % of patients with suspected malignant stenosis were eventually diagnosed with a benign lesion through postoperative histological examination [ 23 , 24 ]. In many cases, diagnosis is based on bile cytology.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly performed diagnostic method for CCA is biliary cytology, which tests the bile sample from a biliary drainage catheter. However, the sensitivity of biliary cytology is extremely low (20.7%±3.5%) as reported in published study 58. In our meta-analysis of the diagnostic capability of markers for CCA, seven prospective trials12 31-32 34 35 55and a retrospective study9 were eligible for diagnostic analysis that showed that the diagnostic capability of CA19-9 was inferior to other molecules, such as WFA-MUC1.…”
Section: Discussionmentioning
confidence: 78%
“…We recently performed a study to determine the effective sampling number to increase the diagnostic accuracy of biliary cytology. 1 This study demonstrated that the positivity of cytology in a onetime sampling session was only 25.6 %. The cumulative positivity was approximately 50 %, even after 10 sampling patients with benign diseases), and we further confirmed the diagnostic value of the WFA-sialylated MUC1 ELISA system for bile samples.…”
Section: Discussionmentioning
confidence: 95%
“…However, the sensitivity of biliary cytology was unexpectedly low in a previous study. 1 Serum carbohydrate antigen 19-9 (CA19-9) also is a commonly used tumor marker for bile duct cancer. However, the level of CA19-9 may be modified by the presence of biliary stricture or hyperbilirubinemia.…”
mentioning
confidence: 99%